2009
DOI: 10.1080/13557850802609949
|View full text |Cite
|
Sign up to set email alerts
|

Cultural identification and smoking among American Indian adults in an urban setting

Abstract: Our data suggest that, among some groups of urban AIs, recreational smoking is associated with AI cultural identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These included associations of tobacco with trauma, the penetration of commercial tobacco into their families and communities, a contrast between ceremonial and commercial forms of tobacco, and an awareness that AI/AN people were directly marked to and targeted to become addicted to commercial cigarettes. Previous qualitative studies with diverse AI/AN groups including discussions of tobacco use confirm a complex relationship between AI/AN identity and tobacco ( Angstman et al, 2009 , Forster et al, 2008 , Burgess et al, 2007 ), and our results suggest these issues are important to acknowledge to deliver effective and acceptable cessation alongside LCS in this population.…”
Section: Discussionsupporting
confidence: 67%
“…These included associations of tobacco with trauma, the penetration of commercial tobacco into their families and communities, a contrast between ceremonial and commercial forms of tobacco, and an awareness that AI/AN people were directly marked to and targeted to become addicted to commercial cigarettes. Previous qualitative studies with diverse AI/AN groups including discussions of tobacco use confirm a complex relationship between AI/AN identity and tobacco ( Angstman et al, 2009 , Forster et al, 2008 , Burgess et al, 2007 ), and our results suggest these issues are important to acknowledge to deliver effective and acceptable cessation alongside LCS in this population.…”
Section: Discussionsupporting
confidence: 67%
“…Oetting and Beauvais (1990–) reported a similar finding in the original paper on Orthogonal Cultural Identification. Similarly, in regard to smoking among urban AI adults, Angstman, Harris, Golbeck, and Swaney () found that AI identification increased risk while white identification decreased risk. While most authors have posited a beneficial influence of both in‐group and out‐group identification, in the case of American Indian youth who are exposed to very high rates of substance use by peers, identification with their own group may actually increase risk for substance use.…”
Section: Discussionmentioning
confidence: 95%
“…The orthogonal cultural identification theory and OCIS have made significant contributions to research in the fields of health, behavioral sciences and social sciences. In one study, Angstman et al (2009), used OCIS to investigate the relationship between cultural identification and smoking among American Indian (AI) adults. They found 1) that high AI identification predicted smoker status and high reservation, 2) orthogonal identification status did not predict smoker status when controlling for age and reservation residence, and 3) positive responses to certain individual OCIS items predicted smoker status when controlling for age and reservation residence.…”
Section: Orthogonal Cultural Identification Theorymentioning
confidence: 99%
“…Cultural identity plays a role in influencing one's process of identifying with another group, as people will bring with them their practices, values, and traditions to the host country or cultures with which they become associated. The interwoven and inseparable nature between cultural identity and identification has been observed in studies, mainly in the fields of health, behavioral sciences and social sciences (Angstman, Harris, Golbeck & Swaney, 2009;Campesino, Belyea, & Schwartz, 2009;Howarth, Wagner, Magnusson, & Sammut, 2014;Lawton & Gerdes, 2014). However, investigation into students' cultural identification and acculturation within the SA context is scarce.…”
mentioning
confidence: 99%